2015
DOI: 10.7243/2055-091x-2-13
|View full text |Cite
|
Sign up to set email alerts
|

DOG1, alpha-amylase and p63 expression in acinic cell carcinoma of salivary gland; immunohistochemical, clinical and radiological study

Abstract: Introduction: Identification of serous acinar differentiation is the basic step for the diagnosis of acinic cell carcinoma (ACC). α-amylase was described to be specific for normal acinar cell but its affinity to malignant counterpart is being contentious. Recently discovered marker anoctamin (DOG1) specific for diagnosis of GISTs has been reported for its efficacy to stain the malignant acinar cells and so, it is being of value in ACC diagnosis. On the other hand, negativity of acinar cells to basal cell marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…In a study of 14 cases of salivary gland acinic cell carcinoma by Ihab Shafek Atta et al, all ACCs (100%) revealed positivity with DOG1 staining and the authors concluded that DOG1 has a higher efficacy in the diagnosis of ACC than α-amylase. (10) The common pattern of DOG1 staining observed is that of intense apical membranous staining around lumina as in our case as well as complete membranous and variable cytoplasmic staining. (5) CONCLUSION Acinic cell carcinoma arising in nasal cavity is extremely uncommon.…”
Section: Discussionmentioning
confidence: 84%
“…In a study of 14 cases of salivary gland acinic cell carcinoma by Ihab Shafek Atta et al, all ACCs (100%) revealed positivity with DOG1 staining and the authors concluded that DOG1 has a higher efficacy in the diagnosis of ACC than α-amylase. (10) The common pattern of DOG1 staining observed is that of intense apical membranous staining around lumina as in our case as well as complete membranous and variable cytoplasmic staining. (5) CONCLUSION Acinic cell carcinoma arising in nasal cavity is extremely uncommon.…”
Section: Discussionmentioning
confidence: 84%
“…1A ). An additional immunohistochemical (IHC) study with glypican 3 3 and HepPar1 4 staining confirmed the diagnosis of metastatic HCC in the stomach ( Fig. 2G and H ).…”
Section: Case Reportmentioning
confidence: 75%
“…Given extensive experimental evidence suggesting a central role for YAP‐1 in LR, we initially assessed intrahepatic YAP‐1 levels and dynamics in patients undergoing major liver resection. Baseline YAP‐1 expression was primarily found in ductular structures in the resting liver, as evaluated via co‐localization of YAP‐1 (marker reference 33 ) and CK19 (marker reference 34 ) upon immunofluorescence imaging (Figure 1). We then assessed tissue from the same patients obtained 2 h after induction of regeneration (study design illustrated in Figure 1A).…”
Section: Resultsmentioning
confidence: 99%